IDEOLOGICAL FOUNDATIONS OF SPIRITUAL DEVELOPMENT - Ilhom Fayzullayev (Western European Studies, 2025)
In this article, his views on the ideological foundations of spiritual growth in society are analyzed from a scientific perspective. The article also scientifically illuminates that spiritual growth is often closely linked to national and religious values, spiritual heritage, universal values, and patriotism, and these processes serve as the foundation for the formation of a new spiritual space
Keywords: Society; strategy; spiritual space; ideology